Magnetoelectric coupling of LaFeO3/BiFeO3 heterostructures - Aguiar, E. C.; Ramirez, M. A.; Cortes, J. A.; Rocha, L. S.; Borsari, E.; Simões, A. Z. (Elsevier, 2015)
BiFeO3 (BFO) and LaFeO3 (LFO) heterostructures were obtained at room temperature on Pt/TiO2/SiO2/Si (100) substrates by chemical solution deposition. The films were coherently grown at a temperature of 500°C for 2h. The magnetoelectric coefficient measurement was performed to show magnetoelectric coupling behavior of such heterostructures. The bottom BFO layer in the heterostructure was able to promote the grain growth of the LFO during the annealing process resulting in huge crystal size. Dielectric permittivity and dielectric loss measurements demonstrated only slight dispersion with frequency due to the lower two-dimensional stress in the plane of the film. Improvement of the P-E hysteresis loop was observed for the heterostructure due the decrease of leakage current caused by the LFO sublayer. Room temperature magnetic coercive field measurements indicate that the LFO and LFO/BFO present different magnetic behavior. The magnetic behavior of the heterostructure is influenced by the crystallite size.
Keywords: Ceramics; Chemical synthesis; Coatings; Thin films